Toward a global description of the nucleus-nucleus interaction - Chamon, L. C.; Carlson, B. V.; Gasques, L. R.; Pereira, D.; De Conti, C.; Alvarez, MAG; Hussein, M. S.; Ribeiro, MAC; Rossi, E. S.; Silva, C. P. (American Physical Soc, 2002)
Extensive systematizations of theoretical and experimental nuclear densities and of optical potential strengths extracted from heavy-ion elastic scattering data analyses at low and intermediate energies are presented. The energy dependence of the nuclear potential is accounted for within a model based on the nonlocal nature of the interaction. The systematics indicates that the heavy-ion nuclear potential can be described in a simple global way through a double-folding shape, which basically depends only on the density of nucleons of the partners in the collision. The possibility of extracting information about the nucleon-nucleon interaction from the heavy-ion potential is investigated.